Total Colonic Tubular Duplication Including Terminal Ileum and Appendix: A Rare Case - Sarac, Mehmet; Tartar, Tugay; Bakal, Unal; Kazez, Ahmet (Galenos Yayincilik, 2021)
Total colonic duplications are rare. This case is reported here in order to discuss the treatment of tubular duplication of the entire colon, appendix and terminal ileum. A 2-year-old girl was admitted with complaints of vomiting, abdomen distension, and defecation difficulty. During laparotomy, a tubular duplication with separate mesentery which had no common intestinal wall was detected at the last 20 cm of the ileum. This duplication continued with a common wall and mesentery from the cecum to the sigmoid colon ending blindly. Resection anastomosis was performed for the completely separated tubular duplication at the terminal ileal segment. The remaining tubular duplication, continuing along the cecum, appendix and colon, could not be resected because of its common mesentery, vascular system, and wide common wall with the normal colon. Colotomy performed at the site of sigmoid colon allowed for the opening of the distal of the cyst to normal colon lumen. Gastrointestinal duplication cysts should be kept in mind in patients with chronic abdominal distension. Surgical treatment methods differ because of the different features and localizations of this tubular duplication.
Keywords: Total colonic tubular duplication; surgical treatment; child